IMPACT OF COVID-19 IN PATIENTS WITH CANCER: A SCOPING REVIEW - Silva,Tâmara Taynah Medeiros da (2021)
ABSTRACT Objective: to map the knowledge about SARS-CoV-2 infection in patients with cancer in terms of clinical manifestations, treatment, and prognosis. Method: a scoping review based on the Joanna Briggs Institute theoretical framework, registered in the Open Science Framework (osf.io/64ems/). A search was carried out in nine databases and virtual libraries in June and July 2020. Results: twenty-five articles were selected that answered the guiding question, demonstrating that the neoplasm most affected by the infection was the lung, and the main clinical manifestations were fever, cough, dyspnea, diarrhea, and fatigue. Regarding treatment, antivirals and antibiotics were the most mentioned. All articles cite the vulnerability of patients with cancer diagnosed with COVID-19, with a mortality rate of 21-30% in most articles and a prognosis for progression to severe forms of the disease. Still, most patients were cured, although in severe cases they worsened, compared to the general population. Conclusion: this study demonstrated insecurity in disease treatment due to the variety of medications used and the uncertainty about whether to continue neoplastic treatment during this period.